Marketing of menthol cigarettes and consumer perceptions - Rising, Joshua (BioMed Central, 2011)
In order to more fully understand why individuals smoke menthol cigarettes, it is important to understand the perceptions held by youth and adults regarding menthol cigarettes. Perceptions are driven by many factors, and one factor that can be important is marketing. This review seeks to examine what role, if any, the marketing of menthol cigarettes plays in the formation of consumer perceptions of menthol cigarettes. The available literature suggests that menthol cigarettes may be perceived as safer choices than non-menthol cigarettes. Furthermore, there is significant overlap between menthol cigarette advertising campaigns and the perceptions of these products held by consumers. The marketing of menthol cigarettes has been higher in publications and venues whose target audiences are Blacks/African Americans. Finally, there appears to have been changes in cigarette menthol content over the past decade, which has been viewed by some researchers as an effort to attract different types of smokers.